2013
DOI: 10.5539/esr.v2n2p52
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Global Oil Spill Modeling System

Abstract: This paper describes the development of an oil spill modeling system that is operational on a global scale and can be used for both real-time response, forecast simulations and probabilistic risk analysis based on climatological wind and ocean current data. For ocean and estuarine spills, the system makes use of the General NOAA Operational Modeling Environment (GNOME) oil spill model, Trajectory Analysis Planner and the Automated Data Inquiry for Oil Spills weathering model. Hydrodynamic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The oil slick simulation and tracking are done in Lagrangian coordinates [23,24], by replacing the oil mass by a big number (10 4 )of particles or parcels, each one of which represents a group of oil droplets of similar size and composition. The oil spill simulation by a large number of passive (not interacting with the existing hydrodynamics) particles, transported in a Lagrangian frame of reference, is the most effective procedure, used in most contemporary models as: (a) it can describe oil spill geometries and shapes at subgrid level, (b) the model results are not distorted by numerical errors, like numerical diffusion, and (c) the fraction of the initially introduced particles (at the spill source) reaching the coast can be considered as the probability of pollution from a minor spill [25]. According to the tracer technique, it is theoretically possible to track the motion of all the "particles" (parcels) of an oil plume as they are transported by the sea.…”
Section: Model Constructionmentioning
confidence: 99%
“…The oil slick simulation and tracking are done in Lagrangian coordinates [23,24], by replacing the oil mass by a big number (10 4 )of particles or parcels, each one of which represents a group of oil droplets of similar size and composition. The oil spill simulation by a large number of passive (not interacting with the existing hydrodynamics) particles, transported in a Lagrangian frame of reference, is the most effective procedure, used in most contemporary models as: (a) it can describe oil spill geometries and shapes at subgrid level, (b) the model results are not distorted by numerical errors, like numerical diffusion, and (c) the fraction of the initially introduced particles (at the spill source) reaching the coast can be considered as the probability of pollution from a minor spill [25]. According to the tracer technique, it is theoretically possible to track the motion of all the "particles" (parcels) of an oil plume as they are transported by the sea.…”
Section: Model Constructionmentioning
confidence: 99%
“…Some previous studies integrated atmospheric and hydrodynamic datasets with the full oil spill transport and fate models (French et al, 1999;Abascal et al, 2010;Daniel et al, 2011;Singkran, 2013;Zelenke et al, 2012). Others used simplified oil spill models (Olita et al, 2012) or replaced oil by a system of passive tracers (Price et al, 2003(Price et al, , 2004Galt and Payton, 1999;Barker and Galt, 2000;Samuels et al, 2013;Pizzigalli et al, 2007). Although in some studies oil spill models were not used (Ronza et al, 2006;Grifoll et al, 2010), they nonetheless suggested useful approaches to assess hazards and risks that arise from operational oil discharges http://dx.doi.org/10.1016/j.marpolbul.2014.10.039 0025-326X/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 97%
“…The oil spill simulation by a large number of passive (not interacting with the existing hydrodynamics) particles, transported in a Lagrangian frame of reference, is the most effective procedure, used in most contemporary models as a) it can describe oil spill geometries and shapes at subgrid level, b) the model results are not distorted by numerical errors, like numerical diffusion, and c) the fraction of the initially introduced (at the spill source) particles reaching the coast can be considered as the probability of pollution from a minor spill (Samuels et al, 2013).…”
Section: Methodsmentioning
confidence: 99%